Corpus-Based Analysis of Online Hoax Discourse on Transportation Subject Picturing Indonesian Issue - Yune Andryani Pinem (Lingua Cultura, 2021)
The research discussed Indonesian hoax on transportation, spread using chain messages over social media, a major hoax subject. Setting social structure as an element to consider in hoax discourse gave different perspectives on why hoax news took place. Contrasting identified online hoax discourse to corpus-derived prosody could be interpreted using a socio-pragmatic approach by Lin and Chung (2016). The research tried to look at how discourse on hoax correlated to real social issues among Indonesian people. Digital forensic was done by tracking discourse used as data from hoax news collection on turnbackhoax.com during 2017-2019. Discourse was later generated into clusters of subject idea of ‘tilang’, ‘jalan tol’, public land transport and infrastructure, ‘kecelakaan pesawat’, ‘lowongan kerja’, ‘China’, insecurity toward government and ‘kecelakaan kapal’. The subject idea was later consulted to Indonesian Web Corpus (IWaC). Through the socio-pragmatic approach, prosody derived by contrasting process portrayed hoax on transportation as a reflection of unsolved current social problems among Indonesian community including distrust toward the government, unawareness on transport safety, law and regulation, economic status, and trend. The finding of the research is recommended to take action toward those problems to eliminate hoax spread in the transportation sector.